1976
DOI: 10.1111/j.2044-8295.1976.tb01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Were Cattell's ‘Personality Sphere’ Factors Correctly Identified in the First Instance?

Abstract: Cattell's system of personality factors has not changed in essentials since his foundation 'personality sphere' studies of 30 yeam ago, although the original 12 factor (A through L) system has been extended and has found worldwide application in the Sixteen Personality Factor Questionnaire (16 PF). The article begins with a summary of recent criticisms of the latter, as reflecting upon Cattell's system, and then proceeds to a specific re-examination of the foundations of that system in order to put the questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 9 publications
1
19
0
1
Order By: Relevance
“…This condition is very much in line with equity theory and expectancy theory, as well as the model of perception proposed by Potter and Lawler (1986). This result is also consistent with the results of the study done by Hogan (1983), Howarth (1976), andZimmerman (2008). This finding also becomes a reason to accept the hypothesis stating that openness to Experience reinforces the impact of CEO"s perception on the compensation toward the turnover.…”
Section: Openness To Experience Reinforces the Impact Of Ceo's Percepsupporting
confidence: 82%
See 2 more Smart Citations
“…This condition is very much in line with equity theory and expectancy theory, as well as the model of perception proposed by Potter and Lawler (1986). This result is also consistent with the results of the study done by Hogan (1983), Howarth (1976), andZimmerman (2008). This finding also becomes a reason to accept the hypothesis stating that openness to Experience reinforces the impact of CEO"s perception on the compensation toward the turnover.…”
Section: Openness To Experience Reinforces the Impact Of Ceo's Percepsupporting
confidence: 82%
“…In the case, the Emotional Stability or Neuroticism is positively related to the desire to leave, while Conscientiousness and Agreeableness is negatively related to the turnover decision. Openness has, on the contrary, a positive direct effect on turnover, possibly because the individual that has this sort of personality is open to find a job in the new environment (Hogan 1983), has a broad requirement (interest) (Costa and McCrae 1985;Fiske 1949) or easily switches orientation (Howarth 1976), in Zimmerman (2008. Extraversion has been found to have a correlation with the degree of 4% towards the turnover and, thus, it is not significant.…”
Section: Theoretical Framework and Hypo-thesismentioning
confidence: 95%
See 1 more Smart Citation
“…One of the few personality dimensions that most personality theorists agree is robust enough to identify from study to study and investigator to investigator is that of introversion/extraversion. It has been shown that this personality dimension can be identified in such varied item sets as behavioral measures (Eysenck, 1947), peer ratings, and self-report inventories (Cat-tell, 1957(Cat-tell, , 1973Howarth, 1976;Norman, 1969). Introversion/extraversion has also been identified as a prominent factor in a set of items sampled from all major personality inventories (Browne & Howarth, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…The I/E dimension has been identified in behavioral measures (H. J. Eysenck, 1947), peer ratings, and self-report inventories (Cattell, 1957(Cattell, , 1973Howarth, 1976;Norman, 1969). It has also been found to be a prominent factor in a set of items sampled from all of the major personality inventories (Browne & Howarth, 1977).…”
Section: Introversion-extroversion and Arousalmentioning
confidence: 99%